أثار قضية بوسمان في تعديل نظام الانتقال الدولي للاعبي كرة القدم المحترفين - الخابور, ساجر; حمودي, طارق (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The case of Belgian player Jean-Marc Bousman is a very important turning point for contemporary football as the transfer system has been completely modified as the regulations restrict the transfer of professional football players so that the player's fate is tied to the club's will, The fate of the players. This system of transfer was conflict with the provisions of the Rome Treaty on the European Economic Area, in particular with regard to the principle of free movement of labor between States, as provided for in article 48 of the Treaty .The player appealed to the European Court of Justice against the provisions of the transfer, demanding the cancellation of the condition of nationality provided for in the rules of the European Football Federation (UEFA) and also to challenge the rules that grant the right to transfer Fee after the completion of the contract stipulated in the regulations of the International Football Association (FIFA). Indeed, the Court recognized the violation of the transition regime to the provisions of the European Treaty, which had the effect of amending the rules of international transition and giving the players more freedom. تُعتبر قضية اللاعب البلجيكي جان مارك بوسمان نقطة تحول غاية في الأهمية بالنسبة لكرة القدم المعاصرة إذ ترتب عليها تعديل نظام الانتقال بشكل كلي بعد أن كانت اللوائح تٌقيد عملية انتقال لاعبي كرة القدم المحترفين على نحو يجعل من مصير اللاعب مرتبطاً بإرادة النادي والذي كانت يتمتع نتيجة ذلك بسلطة التحكم بمصير اللاعبين. وهذا النظام للانتقال كان يتعارض مع أحكام معاهدة روما الخاصة بالمنطقة الاقتصادية الأوربية ولاسيما فيما يتعلق بمبدأ حرية تنقل العمالة بين الدول والذي نصت عليه المادة 48 من الاتفاقية. وقد قام اللاعب بالطعن أمام محكمة العدل الأوربية ضد أحكام الانتقال مطالباً بإلغاء قيد الجنسية المنصوص عنه في لوائح الاتحاد الأوربي لكرة القدم وكذلك الطعن بالقواعد التي تمنح الحق ببدل الانتقال بعد انتهاء العقد المنصوص عنها في لوائح الاتحاد الدولي لكرة القدم. وبالفعل فقد أقرت المحكمة بمخالفة نظام الانتقال لأحكام المعاهدة الأوربية الأمر الذي ترتب عليه تعديل قواعد الانتقال الدولي ومنح اللاعبين المزيد من الحرية